Euprepina Hull, 1971: revisão das espécies e análise cladística(Diptera, Bombyliidae, Bombyliinae) - Lamas, Carlos José Einicker (1996)
Presents the results of taxonomic studies on Euprepina Hull, 1971 (Diptera, Bombyliidae, Bombyliinae) a neotropical genus that includes nine species. Redescriptions of eight species: E. nuda Hull, 1971, E. amabilis (Wulp, 1881), E. beckeri Lamas & Couri, in press, E. bicincta (Wiedemann, 1830), E. caminaria (Wiedemann, 1830), E. knutsoni Hull, 1971, E. maracajula Hull, 1971 and E. truxalia Hull, 1971, with illustrations of male terminalia, spermathecae and labellum; two synonymies(E. bicincta Hull, 1971 = E. bicincta (Wiedemann, 1830) and E. shannoni Hull, 1971 = E. nuda Hull, 1971), a key to species and a cladogram are presented. E. goyaz Hull, 1971, was not included in this study, because none specimen of this species was examined. The cladogram was obtained from cladistic analysis of the eigth studied species, based on a data matrix with 19 characters and using the program PAUP 3.1.1 (SWOFFORD, 1991). Character states were polarized following outgroup analysis (W ATROUS & WHEELER, 1981; MADDISON et alii, 1984 ), and an hypothetical ancestor was included in the analysis in order to root the tree. The method of successive weighting was used and it resulted in a tree with ci = 0,620 and ri= 0,692. ln the analysis, the monophyly of Euprepina was supported by two synapomorphies: palps two-segmented and r-m crossvein which is placed beyond the apical half of the discal cell. The species were organized in two monophiletics groups, based respectively on the following synapomorphies: presence of black bristles in the posterior margim of scutellum; lateral aedeagal apodem long, exceeding gonocoxae margim (only in ACCTRAN optimization), for the group formed by E. amabilis, E. beckeri, E. bicincta and E. caminaria, and, palps with two colors; distiphalus short, not exceeding the apex of gonocoxites lobe, for the group formed by E. knutsoni, E. maracajula, E. nuda and E. truxalia.